Pengaruh Gaya Kepemimpinan, Motivasi, Disiplin Dan Kepuasan Kerja Terhadap Kinerja Karyawan pada PT. Master Rantauprapat - Ramadhani, Eka Fitri; Siregar, Zulkifli Musannip Efendi; Pristiyono, Pristiyono (Universitas Labuhanbatu, 2021)
This study aims to determine the effect of leadership style, motivation, discipline, and job satisfaction on employee performance at PT. Master Rantauprapat. Data collection in this study was carried out through survey approaches, interviews and documentation. This study has a sample of 40 respondents in which the entire population is sampled. The data analysis tool used in this study was SPSS (Statistical Product Software Solution). The data analysis technique in this research is descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance test (t test), simultaneous significant test (F test), and determination coefficient test (R2). That the F test result is 6,137 with a significant level of 0.000 while the F-test value is 2.64. When compared to the value of fcount6.137> ftabel 2.64 at Î± 5%, the conclusion is that simultaneously the variables of Leadership Style, Motivation, Discipline, and Job Satisfaction on Employee Performance have a positive and significant effect on Employee Performance, that the tcount for the Leadership Style variable is 0.105. Motivation of -2,531, Work Discipline of 3,159, and satisfaction of 0,799 with a significant value of each independent variable (2,866), (0,000). As for the t-table value in the t distribution statistical table with a level of test Î± = 5% and df1 = (k-1) = 5 and df2 = (n-k-1) = (40-5) = 35 of 2.64. Based on the criteria that if the value of tcount> ttable H0 is rejected, on the other hand tcount2.64.), ( 0.799> 2.64.). So it can be concluded that partially the leadership style variable (X1) has a negative and significant effect on employee performance (Y), the motivation variable (X2) has a negative and significant effect on employee performance (Y), the work discipline variable (X3) has a positive and significant effect on employee performance. Employee Performance (Y), and the Satisfaction variable (X4) have a positive and significant effect on Employee Performance (Y).